2017
DOI: 10.2139/ssrn.2930061
|View full text |Cite
|
Sign up to set email alerts
|

'I've Got My Mind Made Up': How Judicial Teleology in Cases Involving Biologically Based Evidence Violates Therapeutic Jurisprudence

Abstract: involving, inter alia, the death penalty, 2 the insanity defense, 3 civil competency, 4 incompetency to stand trial, 5 questions related to malingering, 6 juvenile criminal procedure, 7 and criminal sentencing. 8 And I am not the only one to have pointed this out. 9 Courts are also teleological on the question of admission of evidence in accordance with the rulings in cases such as Daubert and Frye.o There is no reason to doubt Professor Susan Rozelle's glum conclusion that "the game of scientific evidence loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…4 This bias can affect the way FMHEs and legal professionals attend to and the degree to which they believe the experiences of those with whom they interact. There is fairly extensive TJ literature on cognitive biases, their effects on judicial decision making (King et al, 2011), and suggested ways of remediating such biases (Perlin, 2017).…”
Section: Testimony and Educating Triers Of Factmentioning
confidence: 99%
See 2 more Smart Citations
“…4 This bias can affect the way FMHEs and legal professionals attend to and the degree to which they believe the experiences of those with whom they interact. There is fairly extensive TJ literature on cognitive biases, their effects on judicial decision making (King et al, 2011), and suggested ways of remediating such biases (Perlin, 2017).…”
Section: Testimony and Educating Triers Of Factmentioning
confidence: 99%
“…This is consistent with the “just-world fallacy” (Lerner, 1980)—a cognitive bias reflecting a belief in morality and fairness and that “bad things only happen to bad people.” 4 This bias can affect the way FMHEs and legal professionals attend to and the degree to which they believe the experiences of those with whom they interact. There is fairly extensive TJ literature on cognitive biases, their effects on judicial decision making (King et al, 2011), and suggested ways of remediating such biases (Perlin, 2017).…”
Section: Applying Trauma-informed Principles To Forensic Mental Healt...mentioning
confidence: 99%
See 1 more Smart Citation
“…As I have written elsewhere, "An inquiry into therapeutic outcomes does not mean that therapeutic concerns 'trump' civil rights and civil liberties" (Perlin, 2000, p. 412). Therapeutic jurisprudence "look[s] at law as it actually impacts people's lives" (Winick, 2009, p. 535) and TJ supports "an ethic of care" (Perlin, 2008, p. 94, quoting, in part, Winick & Wexler, 2006. It attempts to bring about healing and wellness and to value psychological health (Perlin, 2008, p. 94, citing Winick, 2003.…”
Section: A Therapeutic Jurisprudence Analysismentioning
confidence: 99%
“…Therapeutic jurisprudence "look[s] at law as it actually impacts people's lives" (Winick, 2009, p. 535) and TJ supports "an ethic of care" (Perlin, 2008, p. 94, quoting, in part, Winick & Wexler, 2006. It attempts to bring about healing and wellness and to value psychological health (Perlin, 2008, p. 94, citing Winick, 2003.…”
Section: A Therapeutic Jurisprudence Analysismentioning
confidence: 99%